The Composition Role of the Dialogue in Chernobyl Prayer: A Chronicle of the Future - Штранц-Никитина, Вероника (Poznańskie Studia Slawistyczne, 2020)
The paper deals with some specific features of dialogism in the book Chernobyl Prayer: A Chronicle of the Future by the Belarusian Nobel Laureate Svetlana Alexievich. As the title implies the article investigates typology of the dialogue in the text which is based on the Bakhtin’s analysis of the concept of the dialogue and polyphony. The article describes some principles of dialogism in relation to the composition of the text.